THE EFFECT OF FUNCTIONAL TRAINING, INTEGRITY, COMPETENCY AND ORGANIZATIONAL COMMITMENT OF QUALITY AUDIT IN THE AUDIT BOARD OF REPUBLIC INDONESIA - Edi Sunyoto; Djaali Djaali; Maruf Akbar (IJHCM (International Journal of Human Capital Management), 2017)
This research investigate about the influence of functional training, integrity, competence and organizational commitment to quality audit. The purpose of this research was to determine the effect of functional training, integrity, competence and organizational commitment to quality audit, in The Audit Board of Republic Indonesia, Jakarta in 2017. The research used survey method quantitative approach with path analysis technique. Methods of survey research using quantitative approach path analysis techniques. The data were collected from 100 auditor as sample. Sample were sellected by simple random sampling from 130 Auditor as population. The results showed there is the significant direct effect functional of training on quality audit; integrity on qualty audit; competency on quality audit; organizational commitment on quality audit; functional training, Integrity and Competence significant direct effect on organizational commitment; functional training and Integrity significant direct effect on the competence; direct effect on the integrity of functional training is significant.